2022
DOI: 10.1093/mnras/stac3413
|View full text |Cite
|
Sign up to set email alerts
|

The molecular gas main sequence and Schmidt–Kennicutt relation are fundamental, the star-forming main sequence is a (useful) byproduct

Abstract: We investigate the relationship between the star formation rate (SFR), stellar mass (M*) and molecular gas mass ($M_{H_2}$) for local star-forming galaxies. We further investigate these relationships for high-z (z=1-3) galaxies and for the hosts of a local sample of Active Galactic Nuclei (AGN). We explore which of these dependencies are intrinsic and which are an indirect by-product by employing partial correlation coefficients and random forest regression. We find that for local star-forming galaxies, high-z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 57 publications
(108 reference statements)
1
6
0
Order By: Relevance
“…This distribution qualitatively resembles the bimodal distribution of the star-forming main sequence on the SFR−M * diagram (e.g., Noeske et al 2007;Peng et al 2010). The upper part of the M gas -M * diagram has been studied in the literature mainly through molecular gas measurements and is often called the gas mass main sequence (e.g., Saintonge et al 2016;Bolatto et al 2017;Lin et al 2019;Baker et al 2023).…”
Section: Total Gas Mass As a Function Of Stellar Masssupporting
confidence: 56%
“…This distribution qualitatively resembles the bimodal distribution of the star-forming main sequence on the SFR−M * diagram (e.g., Noeske et al 2007;Peng et al 2010). The upper part of the M gas -M * diagram has been studied in the literature mainly through molecular gas measurements and is often called the gas mass main sequence (e.g., Saintonge et al 2016;Bolatto et al 2017;Lin et al 2019;Baker et al 2023).…”
Section: Total Gas Mass As a Function Of Stellar Masssupporting
confidence: 56%
“…Each acts on a different timescale and on different classes of galaxies. Internal mechanisms, such as feedback from star formation (SF) and supermassive black holes, expelling gas from galaxies, or heating the circumgalactic medium (CGM) and therefore preventing accretion of fresh gas, have been widely invoked [11][12][13][14][15][16][17][18]. Environmental effects, such as ram-pressure stripping of the Interstellar Medium (ISM) in galaxy clusters, or stripping of the CGM, are thought to play a major role in low-mass (< 10 10 M ) satellite galaxies; i.e.…”
mentioning
confidence: 99%
“…The SK relation connects the star formation rate (SFR) surface density (Σ SFR ) to the molecular gas surface density (Σ mol ) as Σ SFR ∝ Σ mol n (or, equivalently, Log Σ SFR = n × Log Σ mol + constant). The power index n is found close to unity but varying between 0.7 and 1.4, depending on the galaxy types (late versus early types, mainsequence (MS) versus green valley (GV) versus starburst galaxies, active galactic nucleus (AGN) versus non-AGN hosts; e.g., Colombo et al 2018;Sánchez et al 2018;Kennicutt & De Los Reyes 2021;Lin et al 2022;Baker et al 2023), physical scales (Lin et al 2019b;Ellison et al 2021a;Pessa et al 2021;Baker et al 2022), galactic environments (Pessa et al 2022), large-scale environments (Jiménez-Donaire et al 2023), local conditions of star formation (star-forming versus retired regions; Ellison et al 2021b;Lin et al 2022), and gas tracers (Wong & Blitz 2002;Gao & Solomon 2004;Bigiel et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Among those investigations, the exploration of the molecular gas abundance and its properties at (sub)kiloparsec scales across different galaxy populations has received significant attention owing to the emergence of extensive large optical integral field unit (IFU) surveys and spatial-resolution-matched observations facilitated by the Atacama Large Millimeter/submillimeter Array (ALMA). Recent studies on kiloparsec scales reveal that the star formation efficiency (SFE; SFE mol = Σ SFR /Σ mol ) measured on kiloparsec scales depends on global galaxy properties, such as the global specific SFR (sSFR; Schruba et al 2011;Leroy et al 2013;Colombo et al 2018;Utomo et al 2018;Lin et al 2019b;Brownson et al 2020;Sun et al 2020;Ellison et al 2021a;Lin et al 2022;Baker et al 2023). For example, based on CO (1-0) observations from the ALMA-MaNGA QUEnching and STar formation (ALMaQUEST; Lin et al 2020) survey, Lin et al (2022) found that GV galaxies not only show lower molecular gas fractions ( f mol ), defined as the ratio of the molecular gas surface density to the stellar mass surface density (Σ mol /Σ * ), but also depart from the MS galaxies in the resolved SK (rSK) relation toward a lower value of Σ SFR at a given Σ mol (see also Lin et al 2017;Brownson et al 2020;Ellison et al 2021a).…”
Section: Introductionmentioning
confidence: 99%